Nitrobenzene-induced hormonal disruption, alteration of steroidogenic pathway, and oxidative damage in rat: protective effects of Vernonia amygdalina - Johnson O. Oladele; Oyedotun M. Oyeleke; Oluwaseun T. Oladele; Oluwafeyisayo D. Babatope; Olaide O. Awosanya (Clinical Phytoscience, 2020)
Abstract Background Infertility is a global health burden which affect more than 15% of couples’ population. An impaired hormonal balance, oxidative stress and alteration in the physiological function of the reproductive organ are factors leading to infertility. The present study investigated the protective role of methanolic leaf extract of Vernonia amygdalina (MLVA) against Nitrobenzene-induced oxidative testicular damage and hormonal imbalance in rats. Thirty sexually active male wistar rats were sorted into five groups, each group containing six rats. Group I received distilled water while 100 mg/kg bw of Nitrobenzene was administered to groups (II, III, IV and V) to induce testicular damage and hormonal imbalance. Group III and IV were treated with oral administration of 200 mg/kg bw and 400 mg/kg bw of MLVA respectively and group V with vitamin E for 14 days. Results Nitrobenzene-treated rats showed significant (P < 0.05) decrease in the body weight gain, testis and epididymis weights. However, upon administration of MLVA or vitamin E, these changes were significantly reversed in Nitrobenzene-treated rats. Also, Nitrobenzene significantly (P˂0.05) induced endocrine disruption as shown by decreased activities level of serum Thyroid stimulating hormone (TSH), luteinizing hormone (LH), follicle stimulating hormone (FSH), prolactin, testosterone, triiodothyronine (T3), and tetraiodothyronine (T4). Administration of Nitrobenzene also induced oxidative damage as shown by increased level of testicular lipid peroxidation (MDA), and decreased levels of glutathione (GSH). Histological studies of the testes revealed mild congestion of interstitial vessels and oedema in rats administered Nitrobenzene only. Conclusion Taken together, MLVA obliterated the adverse effects of Nitrobenzene on the antioxidant enzymes, markers of testicular oxidative damage, endocrine and testicular structure in rats.